PERLINDUNGAN ANAK TERHADAP PRAKTIK KEKERASAN PADA POLA ASUH ANAK DI MASYARAKAT ADAT MANGGARAI NTT (PERSPEKTIF UNDANG UNDANG PERLINDUNGAN ANAK) - Helmi Daiyati; Andy Usmina Wijaya (HUKMY : Jurnal Hukum, 2026)
This study aims to analyze the forms of legal protection for children from violent practices in the parenting patterns of the Manggarai indigenous community, East Nusa Tenggara. Violent practices in these parenting patterns are still often considered part of the tradition of educating children, thus contradicting the principles of child protection in Law No. 35 of 2014 concerning “Child Protection”. By applying normative legal research methods, this study highlights the tension between customary legal norms and national law. The results show that the implementation of child protection is not optimal due to the strong influence of local culture. Legal harmonization measures are needed that integrate customary values ​​with the principles of child protection to realize justice and legal balance in society.